The Botany, Chemistry, Pharmacological and Therapeutic Application of Psoralea corylifolia L. – A Review - Shilandra Kumar Uikey; A.S. Yadav; Ajit K. Sharma; Atul K. Rai; D.K. Raghuwanshi; Yogesh Badkhane (International Journal of Phytomedicine, 2010)
Psoralea corylifolia Linn. is an endangered and medicinally important plant indigenous to tropical and subtropical regions of the world. Its medicinal usage is reported in Indian pharmaceutical codex, the Chinese, British and the American pharmacopoeias and in different traditional system of medicines such as Ayurveda, Unani and Siddha. The review reveals that wide ranges of phytochemical constituents have been isolated from the plant and it possesses important activities like antibacterial, antiinflammatory and antitumer. Various other activities like hepatoprotective, antioxidants and antithelminitic have also been reported. These repots are very encouraging and indicate that herb should be studied more expensively for its therapeutic benefits. This article briefly reviews the botany, pharmacology, biochemistry and therapeutic application of the plant. This is an attempt to compile and document information on different aspects of Psoralea corylifolia and highlight the need for research and development.